Sistem Informasi Manajemen Instalasi Gawat Darurat BP-RB PKU Muhammadiyah Pakem, Sleman, Yogyakarta - tumarta, yunita wisda (JUSS (Jurnal Sains dan Sistem Informasi), 2019)
BP-RB PKU Muhammadiyah Pakem is a medical center that is still relatively new and is seriously preparing hardware, software, and brain devices, especially in Emergency Installation (IGD). Patients who come to the emergency room need fast and appropriate assistance. At BP-RB PKU Muhammadiyah Pakem there is a patient registration process, medical records and calculation of payments still made manually so patients must wait for inspection or payment. This makes searching medical records and visiting data examining previous patients longer because they have to look for lines and sheets. The purpose of this study is to establish an Emergency Management Information System that can help health practitioners in the management process in the emergency unit to be faster and easier in finding patient medical records for previous visits and recording patients' medical records so that patients can be treated quickly and accurately . This study uses several steps including: Defining the main problem, Collecting data, Developing information systems, Defining the main problem, Collecting data, Developing information systems. Methods in system development include software requirements analysis, design, implementation, development. The method for building a web-based system using PHP (Hypertext Prepocessor) and database management systems with My SQL.Keywords: System, Manajemen, IGD